Aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material and polymer-based self-lubricating material
By integrating MXene precipitates into the micro-nanofiber network of aramid fiber/nanocellulose, a hybrid interleaving layer with continuous domain-limited structure is constructed, which solves the problem of MXene etching waste and the problem of insufficient performance of self-lubricating materials, and achieves high-performance self-lubricating materials.
Patent Information
- Application Number
- CN202411945895.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
The traditional MXene preparation method generates a large amount of etching waste, resulting in environmental pollution and waste of resources, and insufficient self-lubricating material performance.
The hybrid interwoven layered material of aramid fiber/nanocellulose/MXene precipitate was used to integrate the MXene precipitate into the micro-nanofiber network through mechanical homogenization and freeze-drying processes to construct a hybrid interwoven layer with continuous domain-limited structure.
It effectively solves the problem of MXene etching waste treatment, improves the performance of self-lubricating materials, including reducing friction coefficient, reducing wear, enhancing mechanical strength, and has environmental protection and sustainability advantages.
Smart Images

Figure CN119708570A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricating materials, and in particular to an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material and a polymer-based self-lubricating material. Background Art
[0002] With the continuous development of modern industry, friction and wear problems have become increasingly prominent in various mechanical equipment, tools, transportation and other fields. Self-lubricating materials can not only effectively reduce friction and wear, but also extend the service life of equipment and reduce energy consumption. In recent years, MXene, as an emerging two-dimensional material, has been widely studied due to its excellent mechanical strength, electrical conductivity, thermal conductivity and good lubrication properties. The preparation, functionalization and application of MXene materials in self-lubricating composite materials have become a research hotspot in the field of materials science and engineering.
[0003] The traditional MXene preparation method usually uses hydrogen fluoride (HF) solution to etch the MAX phase (MXene precursor) to obtain MXene flakes. This process can be achieved through chemical vapor deposition (CVD), liquid phase exfoliation and other methods. However, these methods will produce a large amount of MXene etching waste, especially during HF treatment, the resulting MXene precipitates often pollute the environment and cause waste of resources. Therefore, how to effectively utilize these MXene precipitates will not only help protect the environment, but also maximize the utilization value of resources. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material and a polymer-based self-lubricating material. The present invention uses MXene precipitate as a raw material to prepare a hybrid interwoven layered material, which can not only effectively solve the problem of MXene etching waste treatment, but also greatly improve the performance of the self-lubricating material.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, comprising the following steps:
[0007] The MXene precipitate, the aramid fiber aqueous dispersion and the nanocellulose aqueous dispersion are mixed, and mechanical homogenization and freeze-drying are performed in sequence to obtain the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material.
[0008] Preferably, in terms of mass fraction, the amount of the MXene precipitate is 0.5 to 2 parts, the amount of the aramid fiber aqueous dispersion is 30 to 50 parts, and the amount of the nanocellulose aqueous dispersion is 30 to 50 parts;
[0009] The mass concentration of the aramid fiber aqueous dispersion is 2-3%; the mass concentration of the nanocellulose aqueous dispersion is 1-1.5%.
[0010] Preferably, the method for preparing the MXene precipitate comprises the following steps:
[0011] Mixing T3AlC2 MAX with an acid etching solution to perform an etching reaction to obtain an etching product;
[0012] The etching product is washed with water and separated into solid and liquid, and the obtained solid is dispersed in water, and ultrasonic and centrifuged are performed in sequence to obtain a solid precipitate and an unprecipitated turbid liquid, wherein the solid precipitate is a MXene precipitate.
[0013] Preferably, the method for preparing the aramid fiber aqueous dispersion comprises the following steps:
[0014] The aramid fiber, inorganic strong base, water and organic solvent are mixed to obtain an aramid fiber solution;
[0015] pouring the aramid fiber solution into water for washing and reducing to obtain colloidal aramid fibers;
[0016] The colloidal aramid fiber is mixed with water to obtain an aramid fiber aqueous dispersion.
[0017] Preferably, the mechanical homogenization includes one or more of ultrasonic treatment, ball milling treatment, homogenizer treatment and stirring treatment;
[0018] The freeze-drying temperature is -50 to -56°C and the time is 48 to 56 hours.
[0019] The present invention provides an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material prepared by the above preparation method, comprising a micro-nano fiber network constructed of aramid fibers and nanocellulose, and a MXene precipitate confined in the micro-nano fiber network.
[0020] The present invention provides application of the above-mentioned aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material in the field of lubrication.
[0021] The present invention provides a polymer-based self-lubricating material, comprising the following raw materials in parts by weight:
[0022] 10-20 parts of aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material;
[0023] 50-100 parts of resin matrix;
[0024] 5 to 10 parts of curing agent.
[0025] Preferably, the resin matrix includes one or more of epoxy resin, phenolic resin, polyvinyl alcohol, polyimide, polydimethylsiloxane, polyurethane and unsaturated polyester resin.
[0026] The present invention provides a method for preparing the above-mentioned polymer-based self-lubricating material, characterized in that it comprises the following steps:
[0027] Aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, a resin matrix and a curing agent are mixed and cured and molded to obtain a polymer-based self-lubricating material.
[0028] The present invention provides a method for preparing an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material (denoted as ANF / CNF / MS hybrid material), comprising the following steps: mixing MXene precipitate, aramid fiber aqueous dispersion, and nanocellulose aqueous dispersion, and sequentially performing mechanical homogenization and freeze drying to obtain an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material. The present invention uses MXene precipitate as a raw material, and constructs a hybrid interwoven layer with a continuous confined structure by integrating the waste MXene precipitate generated during the MXene etching process into micro-nano fibers. The present invention confines the granular MXene precipitate in the fiber network through the structural self-assembly process of the micro-nano fiber material in a liquid phase environment. On the one hand, it can avoid the pollution of the MXene etching waste to the environment and improve the utilization rate of the waste; on the other hand, the micro-nano fibers composed of aramid fiber and nanocellulose are combined with the MXene precipitate to form a hybrid interwoven layer with a continuous confined structure. This structure can provide multiple lubrication interfaces in the composite material, and promote the distribution and action of the lubricant during the friction process. MXene precipitates are confined in the fiber network, which can avoid the aggregation or flow of particles. The MXene precipitates in the fiber network can act as self-lubricating fillers, forming a self-lubricating film during the friction process, reducing the friction coefficient and reducing wear. In addition, the orderly accumulation of MXene precipitates in the micro-nano fiber network significantly improves the transmission efficiency of energy and mechanical stress in the plane. When used as a self-lubricating filler, it can effectively enhance the mechanical strength of the substrate. Compared with traditional methods for treating MXene precipitates, the present invention not only solves the pollution problem of MXene precipitates, but also improves the comprehensive performance of the material through a green and environmentally friendly technical route, and has significant environmental protection and sustainability advantages.
[0029] The present invention provides a polymer-based self-lubricating material, and the raw materials for preparing the material include the above-mentioned aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, a resin matrix and a curing agent. The present invention introduces the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material into a polymer matrix and treats it through a homogenization technology, and then obtains a flexible polymer-based self-lubricating material with excellent mechanical strength and self-lubricating ability through subsequent thermal curing molding. In the present invention, the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material constructs a dense stacking layer in the polymer matrix, significantly improves the transmission efficiency of energy and mechanical stress in the plane, and greatly improves the mechanical strength and friction performance of the polymer-based self-lubricating material. The polymer-based self-lubricating material prepared by the present invention using micro-nano fibers and MXene precipitates is a flexible material with excellent mechanical properties, ultra-high toughness and ultra-low friction coefficient, and can be customized in shape according to needs, suitable for a variety of industrial applications, especially in scenes requiring flexible sealing and friction reduction, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM image of the MXene precipitate prepared in Example 1;
[0031] Figure 2 This is the SEM image of the ANF prepared in Example 1;
[0032] Figure 3 This is the SEM image of the freeze-dried nanocellulose aqueous solution in Example 3;
[0033] Figure 4 SEM image of the ANF / CNFMS interlaced layer structure (after freeze-drying) prepared in Example 3;
[0034] Figure 5 The friction coefficient curve of the self-lubricating composite material prepared in Example 3;
[0035] Figure 6 This is a stress-strain curve diagram of the self-lubricating composite material prepared in Example 3. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, comprising the following steps:
[0037] The MXene precipitate, the aramid fiber aqueous dispersion and the nanocellulose aqueous dispersion are mixed, and mechanical homogenization and freeze-drying are performed in sequence to obtain the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material.
[0038] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0039] In the present invention, the MXene precipitate is a waste MXene precipitate, and is preferably a centrifugal precipitate after acid etching of T3AlC2MAX. In the present invention, the preparation method of the MXene precipitate preferably comprises the following steps:
[0040] Mixing T3AlC2 MAX with an acid etching solution to perform an etching reaction to obtain an etching product;
[0041] The etching product is washed with water and separated into solid and liquid, and the obtained solid is dispersed in water, and ultrasonic and centrifuged are performed in sequence to obtain a solid precipitate and an unprecipitated turbid liquid, wherein the solid precipitate is a MXene precipitate.
[0042] In the present invention, the components of the acid etching solution include concentrated hydrochloric acid, lithium fluoride and water, the mass concentration of the concentrated hydrochloric acid is preferably 48%, and the water is preferably distilled water. In the present invention, the amount of the concentrated hydrochloric acid is preferably 50 to 60 parts, the amount of lithium fluoride is 2 to 4 parts, and the amount of water is 10 to 15 parts, by mass. As a specific embodiment of the present invention, the amount of the concentrated hydrochloric acid is 50 parts, 55 parts or 60 parts, the amount of the lithium fluoride is 2 parts, 3 parts or 4 parts, and the amount of the water is 10 parts, 12 parts or 15 parts.
[0043] In the present invention, based on the mass fraction of the concentrated hydrochloric acid, the amount of the T3AlC2 MAX is 2 to 4 parts. As a specific embodiment of the present invention, the amount of the T3AlC2 MAX is 2 parts, 3 parts or 4 parts.
[0044] In the present invention, the mixing and etching reaction is preferably carried out in a PTFE conical flask or a PTFE beaker. In the present invention, the etching reaction is preferably carried out under stirring, the temperature of the etching reaction is preferably 40 to 45° C., and the time is preferably 30 to 48 hours.
[0045] In the present invention, the water washing is preferably carried out under centrifugal conditions, the centrifugal speed is preferably 6000-8000 rpm, and the time is preferably 5-8 min. The present invention washes with water until the pH value of the supernatant is ≥6.0. The present invention removes lithium fluoride and concentrated hydrochloric acid in the etching product through the water washing.
[0046] After the water washing, the present invention performs solid-liquid separation, disperses the obtained solid in water, and sequentially performs ultrasonication and centrifugation. In the present invention, the water is preferably distilled water; the amount of the solid is preferably 2 to 3 parts by mass, and the amount of the water is preferably 80 to 100 parts.
[0047] In the present invention, the power of the ultrasound is preferably 800-1000 W, and the time is preferably 3-5 h. In the present invention, the speed of the centrifugation is preferably 3500-4000 rpm, and the time is preferably 60-120 min.
[0048] In the present invention, the solid precipitate obtained after centrifugation is a MXene precipitate, and the unprecipitated turbid liquid obtained is a dispersion of MXene nanosheets. In the present invention, the solid precipitate obtained after centrifugation is preferably dried. In the present invention, the drying is preferably vacuum drying, the drying temperature is preferably 50 to 60° C., and the drying time is preferably 12 to 16 hours.
[0049] In the present invention, the MXene precipitate preferably exists in the form of aggregates, and the particle size of the MXene precipitate is preferably 50 to 70 μm.
[0050] In the present invention, the method for preparing the aramid fiber aqueous dispersion preferably comprises the following steps:
[0051] The aramid fiber, inorganic strong base, water and organic solvent are mixed to obtain an aramid fiber solution;
[0052] pouring the aramid fiber solution into water for washing and reducing to obtain colloidal aramid fibers;
[0053] The colloidal aramid fiber is mixed with water to obtain an aramid fiber aqueous dispersion.
[0054] The present invention mixes aramid fiber, inorganic strong base, water and organic solvent to obtain an aramid fiber solution. In the present invention, the aramid fiber is preferably Kevlar fiber. As a specific embodiment of the present invention, the Kevlar fiber is purchased from DuPont Company of the United States; in the present invention, the inorganic strong base is preferably NaOH and / or KOH, and the organic solvent is preferably dimethyl sulfoxide.
[0055] In the present invention, the mixing method is preferably stirring and mixing, and the stirring time is preferably 4 to 8 hours. In the present invention, the amount of the aramid fiber is preferably 1 to 2 parts by mass, the amount of the inorganic strong base is preferably 1.5 to 3 parts, the amount of water is preferably 2 to 4 parts, and the amount of the organic solvent is preferably 50 to 100 parts. In the present invention, the role of the inorganic strong base in the aramid fiber is to destroy the polymer structure of the Kevlar fiber, promote the degradation and deconstruction of the fiber, and then provide conditions for the preparation of nano-aramid fiber. At the same time, the strong base can also synergize with the organic solvent to enhance its solubility, accelerate the fiber processing process, and remove impurities to improve the purity of the product.
[0056] After obtaining the aramid fiber solution, the present invention pours the aramid fiber solution into water for washing and reducing to obtain colloidal aramid fibers. In the washing process, DMSO is replaced by water, and water cannot dissolve aramid molecules as effectively as DMSO, resulting in enhanced interactions between molecules and the emergence of aggregation or reorganization trends. This change causes the nano-aramid fibers to re-aggregate from a dispersed state to form a colloidal substance.
[0057] After obtaining the colloidal aramid fiber, the present invention mixes the colloidal aramid fiber with water to obtain an aramid fiber aqueous dispersion. In the present invention, the water is preferably distilled water. The present invention has no special requirements for the mixing method, and a mixing method well known to those skilled in the art can be used.
[0058] In the present invention, the mass concentration of the aramid fiber aqueous dispersion is preferably 2-3%; as a specific embodiment of the present invention, the concentration of the aramid fiber aqueous dispersion is 2%, 2.5% or 3%. In the present invention, the length of the aramid fiber in the aramid fiber aqueous dispersion is preferably 500-1500 μm, more preferably 1000-1200 μm.
[0059] In the present invention, the method for preparing the nanocellulose aqueous dispersion preferably comprises the following steps:
[0060] The nanocellulose is mixed with water to obtain a nanocellulose aqueous dispersion.
[0061] In the present invention, the water is preferably distilled water. The present invention has no special requirements for the waterproofing of the mixture, and a mixing method well known to those skilled in the art can be used, such as stirring and mixing.
[0062] In the present invention, the mass concentration of the nanocellulose aqueous dispersion is preferably 1-1.5%; as a specific embodiment of the present invention, the mass concentration of the nanocellulose aqueous dispersion is 1%, 1.2% or 1.5%. In the present invention, the length of the nanocellulose is preferably 500-1000 μm, more preferably 600-800 μm.
[0063] In the present invention, the amount of the MXene precipitate is 0.5 to 2 parts by mass, the amount of the aramid fiber aqueous dispersion is 30 to 50 parts, and the amount of the nanocellulose aqueous dispersion is 30 to 50 parts. As a specific embodiment of the present invention, the amount of the MXene precipitate is 0.5 parts, 1 parts, 1.5 parts or 2 parts, the amount of the aramid fiber aqueous dispersion is 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, and the amount of the nanocellulose aqueous dispersion is 30 parts, 35 parts, 40 parts, 45 parts or 50 parts.
[0064] In the present invention, the mechanical homogenization preferably includes one or more of ultrasonic treatment, ball milling, homogenizer treatment and stirring treatment, and the ultrasonic treatment is preferably tip ultrasonic treatment. In the present invention, the power of the ultrasonic treatment is preferably 800-1000W, and the time is preferably 60-120min; the speed of the ball milling treatment is preferably 300-400rpm, and the time is preferably 6-10h; the speed of the homogenizer treatment is preferably 7000-8000rpm, and the time is preferably 20-30min; the speed of the stirring treatment is preferably 800-1200rpm, and the time is preferably 18-24h.
[0065] In the present invention, the freeze-drying temperature is preferably -50 to -56°C, and the time is preferably 48 to 56 hours. As a specific embodiment of the present invention, the freeze-drying temperature is -50°C, -52°C, -54°C or -56°C, and the freeze-drying time is 48 hours, 50 hours, 52 hours, 54 hours or 56 hours.
[0066] In the present invention, during the process of mechanical homogenization and freeze-drying, the MXene precipitate, aramid fiber and nanocellulose undergo structural self-assembly to construct a hybrid interwoven layer with a continuous confined structure.
[0067] The present invention provides an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material prepared by the above preparation method, comprising a micro-nano fiber network constructed of aramid fibers and nanocellulose, and a MXene precipitate confined in the micro-nano fiber network.
[0068] The present invention provides application of the above-mentioned aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material in the field of lubrication.
[0069] The present invention provides a polymer-based self-lubricating material, comprising the following raw materials in parts by weight:
[0070] 10-20 parts of aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material;
[0071] 50-100 parts of resin matrix;
[0072] 5 to 10 parts of curing agent.
[0073] The polymer-based self-lubricating material provided by the present invention includes 10 to 20 parts by mass of aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, specifically 10 parts, 12 parts, 15 parts, 18 parts or 20 parts.
[0074] Based on the mass fraction of the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, the polymer-based self-lubricating material provided by the present invention includes 50 to 100 parts of a resin matrix, specifically 50 parts, 60 parts, 70 parts, 80 parts, 90 parts or 100 parts. In the present invention, the resin matrix is preferably one or more of epoxy resin, phenolic resin, polyvinyl alcohol, polyimide, polydimethylsiloxane, polyurethane and unsaturated polyester resin.
[0075] Based on the mass fraction of the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, the polymer-based self-lubricating material provided by the present invention includes 5 to 10 parts of a curing agent, specifically 5 parts, 6 parts, 8 parts or 10 parts. In the present invention, the curing agent is preferably one or more of epichlorohydrin, glutaraldehyde, an amine curing agent and a silane crosslinking agent. In the present invention, the amine curing agent is preferably one or more of diaminodiphenylmethane, N-methyl-p-phenylenediamine and 1,3-diaminocyclohexane. In the present invention, the silane crosslinking agent is one or more of methyltriethoxysilane, vinyltriethoxysilane, benzenetriethoxysilane, trimethylchlorosilane and triaminoalkylsilane.
[0076] In the present invention, the curing agent plays a role in cross-linking and curing the resin matrix.
[0077] The present invention provides a method for preparing the above-mentioned polymer-based self-lubricating material, comprising the following steps:
[0078] Aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, a resin matrix and a curing agent are mixed and cured to obtain a polymer-based self-lubricating material.
[0079] In the present invention, the curing temperature is preferably 50-120°C. As a specific embodiment of the present invention, the curing temperature is 50°C, 60°C, 80°C, 100°C or 120°C. In the present invention, the curing time is preferably 12-16h. As a specific embodiment of the present invention, the curing time is 12h, 14h or 16h. In the present invention, the curing method is preferably one or more of coating treatment, hot pressing, compression molding, casting and normal pressure molding.
[0080] The following is a detailed description of an aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material and a polymer-based self-lubricating material provided by the present invention in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0081] In the following examples, the Kevlar fiber length is 500 to 1500 μm;
[0082] The length of nanocellulose is 500 to 1000 μm.
[0083] Example 1
[0084] (1) A method for preparing ANF / CNF / MS hybrid materials, comprising the following steps:
[0085] Step 1: 50 parts of 48 wt% concentrated hydrochloric acid, 2 parts of lithium fluoride and 10 parts of distilled water are added to a PTFE conical flask and uniformly mixed to prepare an etching solution, and 2 parts of T3AlC2 MAX are added to the etching solution, and the mixture is continuously stirred at 40° C. for 30 hours;
[0086] Step 2: Transfer the mixed solution obtained in step 1 to a centrifuge tube and centrifuge and wash with water continuously at 6000 rpm (5 min / time) until the pH value of the supernatant is greater than 6.0;
[0087] Step 3: Disperse 2 portions of the solid product obtained by centrifugation in 80 portions of distilled water for ultrasonic treatment at a power of 800 W for 3 hours;
[0088] Step 4: Transfer the dispersion after ultrasonication to a centrifuge tube and centrifuge at 3500 rpm for 60 min. Pour out the unprecipitated turbid liquid to obtain a dispersion containing MXene nanosheets, and the solid matter at the bottom of the centrifuge is the MXene precipitate (MS);
[0089] Step 5: 1 part of Kevlar fiber, 1.5 parts of KOH and 2 parts of distilled water were added together into 50 parts of dimethyl sulfoxide, and the mixture was stirred for 4 hours to form an aramid fiber (ANF) solution;
[0090] Step 6: Pour the ANF solution into distilled water to wash and restore the colloidal ANF, and disperse the cleaned ANF in distilled water to prepare an ANF water dispersion with a mass concentration of 2.0%;
[0091] Step 7: Disperse nanocellulose (CNF) in distilled water and ensure that its mass concentration is 1.0%. Mix 30 parts of nanocellulose aqueous dispersion, 30 parts of ANF aqueous dispersion and 0.5 parts of MXene precipitate and process them through a homogenizer (8000 rpm, 20 min) and freeze-drying at -50 °C for 48 hours to allow them to undergo structural self-assembly to obtain ANF / CNF / MS hybrid material.
[0092] (2) A method for preparing a polymer-based self-lubricating material, comprising the following steps:
[0093] 10 parts of freeze-dried ANF / CNF / MS hybrid material were added to 50 parts of polyvinyl alcohol resin matrix and 5 parts of curing agent epichlorohydrin were added, and then it was cross-linked and cured at 50°C for 12 hours by casting to obtain a polymer-based self-lubricating material.
[0094] Example 2
[0095] (1) A method for preparing ANF / CNF / MS hybrid materials, comprising the following steps:
[0096] Step 1: Add 60 parts of 8% concentrated hydrochloric acid, 4 parts of lithium fluoride and 15 parts of distilled water into a PTFE conical bottle and mix them evenly to prepare an etching solution, and add 4 parts of T3AlC2 MAX into the etching solution, and stir the mixture at 45°C for 48 hours;
[0097] Step 2: Transfer the mixed solution obtained in step 1 to a centrifuge tube and centrifuge and wash with water continuously at 8000 rpm (8 min / time) until the pH of the supernatant is greater than 6.0;
[0098] Step 3: Disperse 3 portions of the solid product obtained by centrifugation in 100 portions of distilled water and perform ultrasonic treatment at a power of 1000 W for 5 hours;
[0099] Step 4: Transfer the dispersion after ultrasonication to a centrifuge tube and centrifuge it continuously at 4000 rpm for 120 min. Pour out the unprecipitated turbid liquid to obtain a dispersion containing MXene nanosheets, and the solid matter at the bottom of the centrifuge is the MXene precipitate (MS);
[0100] Step 5: 2 parts of Kevlar fiber, 3 parts of KOH and 4 parts of distilled water are added together into 100 parts of dimethyl sulfoxide, and the mixture is stirred for 8 hours to form an aramid fiber (ANF) solution;
[0101] Step 6: Pour the ANF solution into distilled water to wash and restore the colloidal ANF, and disperse the cleaned ANF in distilled water to prepare an ANF water dispersion with a mass concentration of 3.0%;
[0102] Step 7: Disperse nanocellulose (CNF) in distilled water and ensure that its mass concentration is 1.5%. Mix 50 parts of nanocellulose aqueous dispersion, 50 parts of ANF aqueous dispersion and 2.0 parts of MXene precipitate and perform structural self-assembly by tip ultrasonic treatment (1000W, 60min) and freeze-drying at -56°C for 56 hours to obtain ANF / CNF / MS hybrid material.
[0103] (2) A method for preparing a polymer-based self-lubricating material, comprising the following steps:
[0104] 20 parts of freeze-dried ANF / CNF / MS hybrid material were added to 100 parts of polyvinyl alcohol resin matrix and 10 parts of curing agent epichlorohydrin were added, and then it was cross-linked and cured at 60°C for 16 hours by casting to obtain a polymer-based self-lubricating material.
[0105] Example 3
[0106] (1) A method for preparing ANF / CNF / MS hybrid materials, comprising the following steps:
[0107] Step 1: Add 60 parts of 48 wt% concentrated hydrochloric acid, 3 parts of lithium fluoride and 10 parts of distilled water into a PTFE conical flask and mix them evenly to prepare an etching solution, and add 3 parts of T3AlC2 MAX into the etching solution, and stir the mixture at 45°C for 36 hours;
[0108] Step 2: Transfer the mixed solution obtained in step 1 to a centrifuge tube and centrifuge and wash with water continuously at 6000 rpm (8 min / time) until the pH of the supernatant is greater than 6.0;
[0109] Step 3: Disperse 2 portions of the solid product obtained by centrifugation in 100 portions of distilled water and perform ultrasonic treatment at a power of 1000 W for 4 hours;
[0110] Step 4: Transfer the dispersion after ultrasonication to a centrifuge tube and centrifuge it continuously at 4000 rpm for 120 min. Pour out the unprecipitated turbid liquid to obtain a dispersion containing MXene nanosheets, and the solid matter at the bottom of the centrifuge is the MXene precipitate (MS);
[0111] Step 5: 2 parts of Kevlar fiber, 2 parts of KOH and 3 parts of distilled water were added together into 100 parts of dimethyl sulfoxide, and the mixture was stirred for 8 hours to form an aramid fiber (ANF) solution;
[0112] Step 6: Pour the ANF solution into distilled water to wash and restore the colloidal ANF, and disperse the cleaned ANF in distilled water to prepare an ANF aqueous dispersion with a mass concentration of 2.0%;
[0113] Step 7: Disperse nanocellulose (CNF) in distilled water and ensure that its mass concentration is 1.5%, mix 40 parts of nanocellulose aqueous dispersion, 40 parts of ANF aqueous dispersion and 1.0 part of MXene precipitate and perform structural self-assembly by tip ultrasonic treatment (800W, 120min) and freeze-drying at -56°C for 50 hours to obtain ANF / CNF / MS hybrid material.
[0114] (2) A method for preparing a polymer-based self-lubricating material, comprising the following steps:
[0115] 15 parts of freeze-dried ANF / CNF / MS hybrid material were added to 80 parts of polyvinyl alcohol resin matrix and 5 parts of curing agent epichlorohydrin were added, and then it was cross-linked and cured at 60°C for 12 hours by casting to obtain a polymer-based self-lubricating material.
[0116] Example 4
[0117] (1) A method for preparing ANF / CNF / MS hybrid materials, comprising the following steps:
[0118] Step 1: Add 50 parts of 48% concentrated hydrochloric acid, 3 parts of lithium fluoride and 10 parts of distilled water into a PTFE conical bottle and mix them evenly to prepare an etching solution, and add 3 parts of T3AlC2 MAX into the etching solution, and stir the mixture at 45°C for 48 hours;
[0119] Step 2: Transfer the mixed solution obtained in step 1 to a centrifuge tube and centrifuge and wash with water continuously at 6000 rpm (8 min / time) until the pH of the supernatant is greater than 6.0;
[0120] Step 3: Disperse 3 portions of the solid product obtained by centrifugation in 100 portions of distilled water and perform ultrasonic treatment at a power of 1000 W for 5 hours;
[0121] Step 4: Transfer the dispersion after ultrasonication to a centrifuge tube and centrifuge it continuously at 4000 rpm for 60 min. Pour out the unprecipitated turbid liquid to obtain a dispersion containing MXene nanosheets, and the solid matter at the bottom of the centrifuge is the MXene precipitate (MS);
[0122] Step 5: 2 parts of Kevlar fiber, 2 parts of KOH and 3 parts of distilled water were added together into 100 parts of dimethyl sulfoxide, and the mixture was stirred for 8 hours to form an aramid fiber (ANF) solution;
[0123] Step 6: Pour the ANF solution into distilled water to wash and restore the colloidal ANF, and disperse the cleaned ANF in distilled water to prepare an ANF water dispersion with a mass concentration of 3.0%;
[0124] Step 7: Disperse nanocellulose (CNF) in distilled water and ensure that its concentration is 1.5%. Mix 50 parts of nanocellulose aqueous dispersion, 50 parts of ANF aqueous dispersion and 2.0 parts of MXene precipitate and perform structural self-assembly by tip ultrasonic treatment (800 W, 90 min) and freeze-drying at -56 °C for 56 h to obtain ANF / CNF / MS hybrid material.
[0125] (2) A method for preparing a polymer-based self-lubricating material, comprising the following steps:
[0126] 10 parts of freeze-dried ANF / CNF / MS hybrid material were added to 100 parts of epoxy resin matrix and 5 parts of amine curing agent (model F0716, the main components of which include diphenylmethanediamine and cyclohexanediamine), and then cast and cross-linked and cured at 120°C for 12 hours to obtain a polymer-based self-lubricating material.
[0127] Example 5
[0128] (1) A method for preparing ANF / CNF / MS hybrid materials, comprising the following steps:
[0129] Step 1: Add 55 parts of 48% concentrated hydrochloric acid, 3 parts of lithium fluoride and 15 parts of distilled water into a PTFE conical bottle and mix them evenly to prepare an etching solution, and add 3 parts of T3AlC2 MAX into the etching solution, and stir the mixture at 45°C for 48 hours;
[0130] Step 2: Transfer the mixed solution obtained in step 1 to a centrifuge tube and centrifuge and wash with water continuously at 6000 rpm (6 min / time) until the pH of the supernatant is greater than 6.0;
[0131] Step 3: Disperse 3 portions of the solid product obtained by centrifugation in 100 portions of distilled water and perform ultrasonic treatment at a power of 800 W for 5 hours;
[0132] Step 4: Transfer the dispersion after ultrasonication to a centrifuge tube and centrifuge it continuously at 3500 rpm for 90 min. Pour out the unprecipitated turbid liquid to obtain a dispersion containing MXene nanosheets, and the solid matter at the bottom of the centrifuge is the MXene precipitate (MS);
[0133] Step 5: 2 parts of Kevlar fiber, 2 parts of KOH and 3 parts of distilled water were added together into 100 parts of dimethyl sulfoxide, and the mixture was stirred for 8 hours to form an aramid fiber (ANF) solution;
[0134] Step 6: Pour the ANF solution into distilled water to wash and restore the colloidal ANF, and disperse the cleaned ANF in distilled water to prepare an ANF aqueous dispersion with a mass concentration of 2.0%;
[0135] Step 7: Disperse nanocellulose (CNF) in distilled water and ensure that its concentration is 1.0%. Mix 50 parts of nanocellulose aqueous dispersion, 50 parts of ANF aqueous dispersion and 2.0 parts of MXene precipitate and perform structural self-assembly by tip ultrasonic treatment (800 W, 120 min) and freeze-drying at -56 °C for 56 h to obtain ANF / CNF / MS hybrid material.
[0136] (2) A method for preparing a polymer-based self-lubricating material, comprising the following steps:
[0137] 10 parts of freeze-dried ANF / CNF / MS hybrid material were added to 50 parts of polydimethylsiloxane resin matrix and 5 parts of methyltriethoxysilane, and then cast and cross-linked and cured at 100°C for 16 hours to obtain a polymer-based self-lubricating material.
[0138] Performance Testing
[0139] (1) SEM image of the MXene precipitate prepared in Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the obtained MXene precipitates aggregated together and exhibited a very irregular shape, with a particle size range of 50 to 70 μm.
[0140] The SEM image of the ANF prepared in Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that it has a length of several hundred micrometers and can provide excellent mechanical strength and toughness to the polymer-based composite material.
[0141] The SEM image of the freeze-dried nanocellulose (CNF) aqueous solution in Example 3 is as follows: Figure 3 As shown by Figure 3 It can be seen that the liquid environment induces structural self-assembly of CNF, causing it to spontaneously aggregate into a two-dimensional thin layer material with a large-scale layered structure, which provides a basis for the preparation of ANF / CNF / MS hybrid composites.
[0142] The SEM image of the ANF / CNFMS interlaced layer structure (after freeze-drying) prepared in Example 3 is as follows: Figure 4 As shown, the liquid environment and ice template treatment process lead to the aggregation of nano-components and the formation of larger layered structure materials. The MS micro-nanoparticles are confined inside the hybrid interlaced layers, while the layered materials have a large lateral size of hundreds of micrometers.
[0143] (2) The friction coefficient curve of the self-lubricating composite material prepared in Example 3 is as follows: Figure 5 As shown by Figure 5 It can be seen that due to the construction of multi-scale fiber interlaced layers, friction stress can be quickly transmitted in the polymer matrix, resulting in rapid dispersion of friction energy. The lowest friction coefficient of the composite material reaches 0.133, and the degree of surface wear is almost difficult to observe. Because the polymer undergoes matrix deformation during the friction process, there is no obvious material wear, and only slight scratches can be observed. At the same time, MS can promote the phonon transmission effect in the polymer matrix, greatly enhance the transfer of friction heat and friction energy, and construct a strong self-lubricating transfer film at the friction interface, greatly reducing the friction and wear on the surface of the composite material.
[0144] The stress-strain curve of the self-lubricating composite material prepared in Example 3 is shown in FIG. Figure 6 As shown, Figure 6 Tests 1 to 3 in are the number of repetitions. Figure 6 It can be seen that the construction of multi-scale fiber interlaced layers enhances the mechanical strength of the polymer composite material and can bear most of the tensile load, making it have higher tensile strength (greater than 19MPa) and fracture toughness (4.6MJ / m 3 ).
[0145] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a hybrid interwoven layered material of aramid fiber / nanocellulose / MXene precipitate, characterized in that: The following steps are involved: The MXene precipitate, the aramid fiber aqueous dispersion and the nanocellulose aqueous dispersion are mixed, and mechanical homogenization and freeze-drying are performed in sequence to obtain the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material.
2. The preparation method according to claim 1, characterized in that: In terms of mass fraction, the amount of the MXene precipitate is 0.5 to 2 parts, the amount of the aramid fiber aqueous dispersion is 30 to 50 parts, and the amount of the nanocellulose aqueous dispersion is 30 to 50 parts; The mass concentration of the aramid fiber aqueous dispersion is 2-3%; the mass concentration of the nanocellulose aqueous dispersion is 1-1.5%.
3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the MXene precipitate comprises the following steps: Mixing T3AlC2 MAX with an acid etching solution to perform an etching reaction to obtain an etching product; The etching product is washed with water and separated into solid and liquid, and the obtained solid is dispersed in water, and ultrasonic and centrifuged are performed in sequence to obtain a solid precipitate and an unprecipitated turbid liquid, wherein the solid precipitate is a MXene precipitate.
4. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the aramid fiber aqueous dispersion comprises the following steps: The aramid fiber, inorganic strong base, water and organic solvent are mixed to obtain an aramid fiber solution; pouring the aramid fiber solution into water for washing and reducing to obtain colloidal aramid fibers; The colloidal aramid fiber is mixed with water to obtain an aramid fiber aqueous dispersion.
5. The preparation method according to claim 1 or 2, characterized in that: The mechanical homogenization includes one or more of ultrasonic treatment, ball milling treatment, homogenizer treatment and stirring treatment; The freeze-drying temperature is -50 to -56°C and the time is 48 to 56 hours.
6. Aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It includes a micro-nano fiber network constructed by aramid fiber and nanocellulose, and MXene precipitates confined in the micro-nano fiber network.
7. Application of the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material according to claim 6 in the field of lubrication.
8. A polymer-based self-lubricating material, characterized in that: The preparation method comprises the following raw materials in parts by weight: 10 to 20 parts of the aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material according to claim 6; 50-100 parts of resin matrix; 5 to 10 parts of curing agent.
9. The polymer-based self-lubricating material according to claim 8, characterized in that: The resin matrix includes one or more of epoxy resin, phenolic resin, polyvinyl alcohol, polyimide, polydimethylsiloxane, polyurethane and unsaturated polyester resin.
10. The method for preparing a polymer-based self-lubricating material according to claim 8 or 9, characterized in that: The following steps are involved: Aramid fiber / nanocellulose / MXene precipitate hybrid interwoven layered material, a resin matrix and a curing agent are mixed and cured and molded to obtain a polymer-based self-lubricating material.
Citation Information
Cited By
ANF / CNF bio-based composite material as well as preparation method and application thereof
CN121628297A